2019
DOI: 10.1155/2019/5613986
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Changes in Astigmatism with Noncycloplegia Refraction and Ocular Biometry in Chinese Primary Schoolchildren

Abstract: Purpose. To assess the changing profile of astigmatism in Chinese schoolchildren and the association between astigmatism changes and ocular biometry. Methods. We examined and followed up 1,463 children aged 6–9 years from Wenzhou, China. We measured noncycloplegic refraction twice each year and tested axial length (AL) and corneal radius of curvature (CRC) annually for two years. We defined clinically significant astigmatism (CSA) as ≤−0.75 diopter (D) and non-CSA astigmatism as ≤0 to >−0.75 D. Results. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
3
3
Order By: Relevance
“…The astigmatism prevalence (26.2%, ≤−0.75 D, 4–12 years of age) was higher in Yunnan (12.7%, ≤−0.75 D, 13–14 years of age), 40 Beijing (10%, ≤−0.75 D, 5–15 years of age), 41 and Wenzhou (20.3%, ≤−0.75 D, 6–9 years of age). 42 Our prevalence was lower than that in other studies, where the prevalence was 42.7% in Guangzhou (≤−0.75 D, 5–15 years old) and 36.3% in Shandong (≤−0.75 D, 4–18 years of age). 4 , 43 Different studies have reported contradictory findings, and we detected correlations with age, region of habitation, sex and myopia refractive error, unlike those reported by Zhao et al, Lin et al and Fotouhi et al 41 , 42 , 44 …”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The astigmatism prevalence (26.2%, ≤−0.75 D, 4–12 years of age) was higher in Yunnan (12.7%, ≤−0.75 D, 13–14 years of age), 40 Beijing (10%, ≤−0.75 D, 5–15 years of age), 41 and Wenzhou (20.3%, ≤−0.75 D, 6–9 years of age). 42 Our prevalence was lower than that in other studies, where the prevalence was 42.7% in Guangzhou (≤−0.75 D, 5–15 years old) and 36.3% in Shandong (≤−0.75 D, 4–18 years of age). 4 , 43 Different studies have reported contradictory findings, and we detected correlations with age, region of habitation, sex and myopia refractive error, unlike those reported by Zhao et al, Lin et al and Fotouhi et al 41 , 42 , 44 …”
Section: Discussioncontrasting
confidence: 81%
“… 42 Our prevalence was lower than that in other studies, where the prevalence was 42.7% in Guangzhou (≤−0.75 D, 5–15 years old) and 36.3% in Shandong (≤−0.75 D, 4–18 years of age). 4 , 43 Different studies have reported contradictory findings, and we detected correlations with age, region of habitation, sex and myopia refractive error, unlike those reported by Zhao et al, Lin et al and Fotouhi et al 41 , 42 , 44 …”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Animal studies have demonstrated that axial elongation is a contributing factor in the development of astigmatism [9,10] . Researchers also found that a longer axial length is a risk factor for developing clinically signi cant astigmatism (≤ -0.75D) in Chinese schoolchildren [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation of the prospective cross-sectional study refraction status of students under cycloplegia and non-cycloplegia, together with ocular biometry, will enhance our understanding of the myopia epidemic, especially in China. However, previous studies reported the individual ocular parameters separately ( 7 – 9 ), evaluated them with a non-cycloplegia situation ( 10 ), or reported narrow age results ( 1 ). In addition, several studies were conducted approximately 10 years ago ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%